JUDGES 'PERCEPTION ANALYSIS IN ASSESSMENT OF HITS AND Kicks IN PENCAK SILAT COMPETITION USING ACCELEROMETER SENSORS - Novia Rozalini; Irfandi; Zikrur Rahmat (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
The objectives of this study were: (1) to determine the accuracy of the assessment of strokes in a Pencak silat competition using an accelerometer sensor, (2) to determine the accuracy of the assessment of kicks in a Pencak silat competition using an accelerometer sensor. This research uses a qualitative approach with descriptive research type. The population in this study were 5 athletes of the Aceh Pencak Silat who were used as the research sample, namely the total sampling. The data collection technique uses a pro logger application and an accelerometer sensor tool. The data analysis technique uses the following steps: 1) Data Reduction, 2) Data Display, and 3) Data Validation. The results and conclusions of this study are as follows: 1) Kicks and punches that are right on target and declared that the jury is valid (have points) are kicks and punches that have a minimum vibration value of the X-axis = 10.27 (m / s) ^ 2, Y = 1.83 (M / s) ^ 2 and Z = -2.40 (m / s) ^ 2, 2) the accuracy of the assessment using an accelerometer sensor can help judges in assessing kicks and punches that are declared valid and right on target.